2 days versus 5 days of postoperative antibiotics for complex appendicitis: a pragmatic, open-label, multicentre, non-inferiority randomised trial. Issue 10374 (4th February 2023) - de Wijkerslooth, Elisabeth M L; Boerma, Evert-Jan G; van Rossem, Charles C; van Rosmalen, Joost; Baeten, Coen I M; Beverdam, Frédérique H; Bosmans, Johanna W A M; Consten, Esther C J; Dekker, Jan Willem T; Emous, Marloes; van Geloven, Anna A W; Gijsen, Anton F; et al.
Summary: Background: The appropriate duration of postoperative antibiotics for complex appendicitis is unclear. The increasing global threat of antimicrobial resistance warrants restrictive antibiotic use, which could also reduce side-effects, length of hospital stay, and costs. Methods: In this pragmatic, open-label, non-inferiority trial in 15 hospitals in the Netherlands, patients with complex appendicitis (aged ≥8 years) were randomly assigned (1:1) to receive 2 days or 5 days of intravenous antibiotics after appendicectomy. Randomisation was stratified by centre, and treating physicians and patients were not masked to treatment allocation. The primary endpoint was a composite endpoint of infectious complications and mortality within 90 days. The main outcome was the absolute risk difference (95% CI) in the primary endpoint, adjusted for age and severity of appendicitis, with a non-inferiority margin of 7·5%. Outcome assessment was based on electronic patient records and a telephone consultation 90 days after appendicectomy. Efficacy was analysed in the intention-to-treat and per-protocol populations. Safety outcomes were analysed in the intention-to-treat population. This trial was registered with the Netherlands Trial Register, NL5946. Findings: Between April 12, 2017, and June 3, 2021, 13 267 patients were screened and 1066 were randomly assigned, 533 to each group. 31 were excluded from intention-to-treat analysis of the 2-day group and 30 from the 5-day group owing to errors in recruitment or consent. Appendicectomy was done laparoscopically in 955 (95%) of 1005 patients. The telephone follow-up was completed in 664 (66%) of 1005 patients. The primary endpoint occurred in 51 (10%) of 502 patients analysed in the 2-day group and 41 (8%) of 503 patients analysed in the 5-day group (adjusted absolute risk difference 2·0%, 95% CI −1·6 to 5·6). Rates of complications and re-interventions were similar between trial groups. Fewer patients had adverse effects of antibiotics in the 2-day group (45 [9%] of 502 patients) than in the 5-day group (112 [22%] of 503 patients; odds ratio [OR] 0·344, 95% CI 0·237 to 0·498). Re-admission to hospital was more frequent in the 2-day group (58 [12%] of 502 patients) than in the 5-day group (29 [6%] of 503 patients; OR 2·135, 1·342 to 3·396). There were no treatment-related deaths. Interpretation: 2 days of postoperative intravenous antibiotics for complex appendicitis is non-inferior to 5 days in terms of infectious complications and mortality within 90 days, based on a non-inferiority margin of 7·5%. These findings apply to laparoscopic appendicectomy conducted in a well resourced health-care setting. Adopting this strategy will reduce adverse effects of antibiotics and length of hospital stay. Funding: The Netherlands Organization for Health Research and Development.